FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN PENYAKIT DIABETES MELITUS (DM) TIPE 2 DI PUSKESMAS SIMPANG IV SIPIN KOTA JAMBI TAHUN 2021 - Yulidar (Universitas Adiwangsa Jambi, 2021)
The World Health Organization (WHO) in 2015, showed that 415 million people with diabetes. The number of cases and prevalence of diabetes has continued to increase over the last few decades. DM occurs because of risk factors, namely factors that cannot be modified and those that can be modified. This study aims to determine the factors that influence the incidence of Type 2 Diabetes Mellitus (DM) at Simpang IV Sipin Health Center Jambi City in 2021. This research is a quantitative analytical research. This research was conducted at the Simpang IV Sipin Health Center on July 5-7, 2021. The population in this study were all patients with Type 2 DM at the Simpang IV Sipin Health Center, Jambi City in January- March 2021 as many as 215 people. The sample in this study were 67 people who were taken by accidental sampling. Data was collected by filling out a questionnaire. Data analysis was carried out univariate and bivariate using chi square test. The results showed that most of the respondents had an age of 45 years as many as 63 respondents (94%), female as many as 36 respondents (53.7%), had a genetic history of 44 respondents (65.7%) and had diabetes mellitus as many as 58 respondents (86.6%). There is a relationship between age and the incidence of diabetes mellitus because the p value is 0.007 <0.05. There was no relationship between gender (p=0.723) and family support (p=0.361) with the incidence of diabetes mellitus because p value > 0.05 The results of this study indicate that age affects the incidence of diabetes mellitus. While gender and genetic factors do not affect diabetes mellitus.For this reason, the puskesmas can provide education to both patients and people at risk of DM to prevent DM by maintaining a good diet (reducing consumption of sweet foods), doing physical activity or physical exercise, controlling body weight and blood sugar levels regularly.